Public Perceptions of Agrichemicals - Ravenswaay, Eileen O. van (Council for Agricultural Science and Technology (CAST), 1995)
Understanding public perceptions, risk perception, and the public, risk acceptability and pesticides, and consumer perceptions of animal drugs.
Keywords: Agrichemicals; Public Perception; Pesticides; Animal Drugs